Young Sheldon. The complete first season [videorecording (DVD)] - Lorre, Chuck; Molaro, Steven (Warner Bros. Home Entertainment, 2018)
For nine-year-old Sheldon Cooper, it isn't easy growing up in East Texas. Being a once-in-a-generation mind capable of advanced mathematics and science is not always helpful in a land where church and football are king. And while the vulnerable, gifted, and somewhat naive Sheldon deals with the world, his very normal family must find a way to deal with him.